IMPROVING ENGLISH LEARNING OUTCOMES THROUGH THE APPLICATION OF RECIPROCAL TEACHING APPROACH TO CLASS VII STUDENTS OF UPTD SMPN 1 PEMALI - Suarni, Nety (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
The learning model or approach applied was the Reciprocal Teaching approach. Reciprocal Teaching is an approach to teaching students about learning strategies. Reverse teaching is a constructivist approach based on the principles of making/asking questions. The problem in this research was how to apply the Reciprocal Teaching approach to seventh grade students at UPTD SMPN 1 Pemali. This study aimed to improve English learning outcomes through the application of the Reciprocal Teaching Approach to seventh grade students of UPTD SMPN 1 Pemali. This research is Classroom Action Research conducted in two cycles. Each cycle consisted of 4 stages. The research procedure included planning, implementing actions, observing and reflecting. The subjects of this study were seventh grade students at UPTD SMPN 1 Pemali, a total of 37 students. The data collection technique used was observation and test. Observation was carried out to observe directly the object of research to take a close look at the activities being carried out. Observation of the learning activities of elementary school students after the observation method had been applied, so that it could be processed into qualitative data and tests as data collection instruments for the purpose of measuring knowledge, intelligence, abilities, or talents possessed by individuals or groups through a written test given to research subjects, then to be processed as quantitative. The results of this study indicated that in cycle 1 the average obtained was 62.70 while in cycle 2 obtained 80.00 of 37 students, where in cycle 1 it was in the low category while in cycle 2 it was in the high category. Based on the results of the research above, it can be concluded that the results of English learning in class VII students at UPTD SMPN 1 Pemali through the applications of the Reciprocal Teaching approach has increased.